An overview of amenorrhea and respective remedies in Traditional Persian Medicine - Abdolmajid Elahi; Aref Fereidooni; Farbod Shahabinezhad; Mehdi Ajdari Tafti; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2016)
Amenorrhea is described as complete absence or cessation of menstruation. Besides conventional treatment approaches, traditional and complementary medical systems have suggested numerous natural medications for management of amenorrhea. Current study aimed to compile the pharmacological reports on amenorrhea from the standpoints of early Persian scholars. Medical and pharmaceutical manuscripts of Persian medicine from 9th to 18th centuries A.D. have been reviewed to extract the critical points and natural remedies. Based on Traditional Persian Medicine (TPM), impairment in uterus, brain and circulation are main causes of amenorrhea. Any obstruction, either anatomical or functional, in uterus and allied organs or tissues may lead the body to this disorder. Concerning herbal therapy of amenorrhea in TPM, 71 medicinal plants related to 35 families were found. The most prevalent families were Apiaceae, Asteraceae, Lamiaceae and Fabaceae, respectively. Usual routes of administration were oral, vaginal and topical. However, there was one report on a medicament, spoken to be effective nasally. Traditionally, emmenagogue medicines should possess diuretic activity to be effective for amenorrhea. All reported remedies were known as diuretic agents. However, this description is not corresponded with what is now accepted as diuretic. On the other hand, only Foeniculum vulgare showed therapeutic effects on amenorrhea in a randomized placebo-controlled trial. Despite lack of novel information on emmenagogue activity of these remedies, design and conducting evidence-based animal or human studies may be beneficial for new drug discovery from traditional knowledge.